Quantifying Tectonic and Geomorphic Interpretations of Thermochronometer Data with Inverse Problem Theory (Communications in Computational Physics, 2011)
Thermochronometer data offer a powerful tool for quantifying a wide rangeof geologic processes, such as the deformation and erosion of mountain ranges, topographicevolution, and hydrocarbon maturation. With increasing interest to quantifya wider range of complicated geologic processes, more sophisticated techniques areneeded. This paper is concerned with an inverse problem method for interpreting thethermochronometer data quantitatively. Two novel models are proposed to simulatethe crustal thermal fields and paleo mountain topography as a function of tectonic andsurface processes. One is a heat transport model that describes the change of temperatureof rocks; while the other is surface process model which explains the change ofmountain topography. New computational algorithms are presented for solving theinverse problem of the coupled system of these two models. The model successfullyprovides a new tool for reconstructing the kinematic and the topographic history ofmountains.